Current’s Fluctuations through Molecular Wires Composed of Thiophene Rings (2018)
ABSTRACT: We study theoretically the electronic transport and quantum fluctuations in single-molecule systems using thiophene rings as integrated elementary functions, as well as the dependence of these properties with the increase of the coupled rings, i.e., as a quantum wire. In order to analyze the current flow through these molecular systems, the thiophene rings are considered to be connected to metal contacts, which, in general terms, will be related to the application of voltages (bias voltages or gate voltages) to generate non-equilibrium behavior between the contacts. Due to the nonlinear behavior that is generated when said voltages are applied, it is possible to observe quantum fluctuations in the transport properties of these molecular wires. For the calculation of the transport properties, we applied a tight-binding approach using the Landauer–Büttiker formalism and the Fischer–Lee relationship, by means of a semi-analytic Green’s function method within a real-space renormalization (decimation procedure). Our results showed an excellent agreement with results using a tight-binding model with a minimal number of parameters reported so far for these molecular systems.